Assessment of self-perceived Leadership skills and job satisfaction among the health care provider in a tertiary care hospital, Tamil Nadu, India - M, Jasmine; Devanbu, Vinoth Gnana Chellaiyan; Ilanchoorian, Divya; Manoharan, Aravind; S, Suganthi (Indian Journal of Community Health, 2024)
Background: The success of an organisation depends upon the employee satisfaction, which in turn is related to the leadership styles. Good medical leadership plays a vital role in building a high-quality healthcare. The objectives of the study are to estimate the self-perceived leadership skills and its impact on the job satisfaction among the health care workers working in a tertiary care hospital, Tamil Nadu. Material and Methods: This study, conducted in a Chennai-based private tertiary care hospital, focused on 109 healthcare workers across specialties. It used a cross-sectional design, employing stratified random sampling and validated questionnaires. Data covered demographic profiles, leadership styles- transformational, transactional and laissez faire, and job satisfaction. Results: Majority of the study participants were females and doctors. 20.2% study participants had high transformational scores and 79.8% had moderate scores. 52.3% and 47.7% had high and moderate transactional scores respectively. 42.2% and 57.8% had high and moderate laissez-faire score respectively. The leadership scores have significant positive correlation with job satisfaction scores with r value of 0.64, 0.43 for transformational, transactional. Conclusion: Leaders with demonstrated transformational skills had a beneficial impact and those who exhibited a laissez-faire attitude had a detrimental impact on job satisfaction among the health professionals.